2002
DOI: 10.1079/phn2001321
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of breast-feeding promotion in hospitals and follow-up survey of mother–infant pairs in Germany: the SuSe Study

Abstract: Objective: To assess breast-feeding promotion in maternity hospitals and breastfeeding prevalences during the first year of life in mother-infant pairs in Germany. Design: Cross-sectional assessment of breast-feeding practices in a random sample of German maternity hospitals by use of a postal questionnaire. Follow-up of motherinfant pairs recruited in the participating hospitals to assess breast-feeding prevalences and infant feeding practices by use of a telephone interview 14 days after birth and food-frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
28
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
10
28
1
3
Order By: Relevance
“…47,48 In particular, dietary patterns and feeding regimes in infancy were found to be very similar to a nationwide study on breastfeeding and infant nutrition. 49 Thus, we think that our study may nevertheless serve as a valuable contribution to the discussion of the hypothesis that early protein intake influences later obesity risk.…”
Section: Discussionmentioning
confidence: 84%
“…47,48 In particular, dietary patterns and feeding regimes in infancy were found to be very similar to a nationwide study on breastfeeding and infant nutrition. 49 Thus, we think that our study may nevertheless serve as a valuable contribution to the discussion of the hypothesis that early protein intake influences later obesity risk.…”
Section: Discussionmentioning
confidence: 84%
“…However, there is no theoretical reason to establish reference values and only few data on dietary fibre intake in this age group exist (Institute of Medicine, 2002). In Germany, weaning is starting with vegetables (primarily carrots), combined with potatoes, meat and plant oil, followed monthly by two cereal-containing paps (Kersting and Dulon, 2002). Therefore, in the DONALD Study the dietary fibre intakes were somewhat higher than those proposed by Agostoni et al (1995).…”
Section: Discussionmentioning
confidence: 89%
“…[4][5][6][7] One study found a dose-response relationship only in crude analysis 8 and three studies found no statistically significant effect of duration of breastfeeding on overweight or obesity in later childhood. [9][10][11] Like in other countries, 12 the prevalence of breastfeeding has increased over the past decades in Germany, since the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) began their campaigns for breastfeeding in the 1980s, [13][14][15] and consequently the extent to which we can generalize from former studies remains limited. Furthermore, most studies have estimated the effect of breastfeeding duration on overweight by using the group of never breastfed children as reference group.…”
Section: Introductionmentioning
confidence: 99%